2010
DOI: 10.1089/scd.2009.0071
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA Expression Profiles in Umbilical Cord Blood Cell Lineages

Abstract: MicroRNAs (miRNAs), important regulators of cellular processes, show specific expression signatures in different blood cell lineages and stages of hematopoietic stem cell (HSC) differentiation, indicating their role in the control of hematopoiesis. Because neonatal blood displays various features of immaturity, we might expect differential miRNA regulation. Herein, we determined miRNA expression profiles of umbilical cord blood (UCB) cell lineages and compared them to those of bone marrow (BM) and peripheral b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
62
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(70 citation statements)
references
References 39 publications
7
62
1
Order By: Relevance
“…In this regard, miRNAs have a crucial role in the induction of differentiation toward myeloid and lymphoid lineages or in the maintenance of self-renewal (41). Several studies have reported a group of miRNAs up-regulated in HPCs isolated from different sources, including those observed in our study (27,31,46,47). However, although miR-155 was also identified in previous studies, herein we validated for the first time its mRNA targets in the context of maintenance of the HPC phenotype.…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…In this regard, miRNAs have a crucial role in the induction of differentiation toward myeloid and lymphoid lineages or in the maintenance of self-renewal (41). Several studies have reported a group of miRNAs up-regulated in HPCs isolated from different sources, including those observed in our study (27,31,46,47). However, although miR-155 was also identified in previous studies, herein we validated for the first time its mRNA targets in the context of maintenance of the HPC phenotype.…”
Section: Discussionsupporting
confidence: 53%
“…Interestingly, the miRNAs whose expression levels increased along time points were mostly described as miRNAs associated with embryonic pluripotency states (miR-302-367 cluster; miR-183) (25,26). Conversely, the miRNAs displaying DD and ED expression trends in CBiPSCs were previously associated with differentiation of ESCs or hematopoiesis (Let-7 family, miR-125b, miR-155, and miR99a) (27)(28)(29)(30) or described to be up-regulated in neoplastic diseases (miR-3162 and miR-3921) (31)(32)(33)(34)(35) (Fig. 3A).…”
Section: Resultsmentioning
confidence: 99%
“…Differences in miRNA expression between umbilical cord and adult BM CD34 þ cells were also investigated. 24 Thirteen miRNAs were differentially expressed between umbilical cord and BM CD34 þ cells: miR-548d, miR-203, miR-1, miR-34a, miR-545, let-7b, miR-429, miR-214, miR-195, miR-520h, miR-518a, miR-519d and miR-517c.…”
Section: Overview Of Mirnas In Regulating Hematopoiesismentioning
confidence: 98%
“…Merkerova et al [232] detected differences in the miRNAs expressed by HSCs obtained from bone marrow and umbilical cord blood. Bone marrow-derived CD34…”
Section: Mirnas Associated With Hscsmentioning
confidence: 99%